Effects of microstructures on the slurry wear properties of X70 pipeline steels - JU Biao; WU Hui-bin; PAN Xue-fu; TANG Di (工程科学学报)
Slurry wear tests of three designed pipeline steels with the same chemical composition but different microstructures were performed by utilizing a wet sand/rubber wheel abrasion test apparatus. The worn surfaces were further investigated by scanning electron microscopy and 3D white light interference analysis to reveal the wear mechanism and the relation between the microstructure and wear resisting perforumnce. It is found that the mass loss increases with the increase of the micro-hardness difference between two phases in the muhiphase strueture when the predominant wear mechanism is micro-ploughing combined with micro-fatigue. That is due to a misfit of micro deformation between the hard phase and the soft phase. Among the three different muhiphase steels with nearly the same mechanical properties, the wear resistance of the granular bainite-acicular ferrite muhiphase structure is the best, followed by the granular bainite-polygonal ferrite structure, and then the lath bainite-polygonal ferrite structure.